Narratives on translation across Eurasia and Africa: from Babylonia to Colonial India - Brentjes, Sonja; Høyrup, Jens Egede; O'Brien, Bruce R. (Contact and transmission, 2022)
The book disentangles histories of translations from their treatment in specialized intellectual fields, making the point that histories of translations are not merely sub-categories of the histories of pre-modern sciences, religion, law, or literature but are in fact histories of cultural practices that cut synchronically and diachronically through the entire textual fabric of the investigated societies.00What has driven acts of translation in the past, and what were the conditions that shaped the results? In this volume, scholars from across the humanities interrogate narratives on the process of translation: by historical translators ranging from ancient Babylonia to early modern Japan and the British Empire, and by academics from the nineteenth to the twentieth centuries who interpreted these translators? practices.00In Part 1 the volume authors reflect on the history of the approaches to the phenomenon of translation in their specific fields of competence in order to learn what shaped the academic questions asked, what theoretical and practical tools were deployed, which arguments were privileged, and why certain kinds of evidence (but not others) were thought to be the basis for understanding the function and purpose of all translation performed in a given culture. 0Part II explores how translators and authors from antiquity to modern times described their own motivations and the circumstances in which they chose to translate. In both parts, the contributors disentangle histories of translation from the specialized intellectual fields (such as science, religion, law, or literature) with which they have been bound in order to make the case that we understand translation best when we take into account all cultural practices and translation activities cutting synchronically and diachronically through the entire societal fabric